GESTURING TOWARD THE VISUAL: VIRTUAL REALITY, HYPERTEXT AND EMBODIED FEMINIST CRITICISM - Guertin, Carolyn (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1999)
Feminist critics have been as slow to take up the tools of electronic scholarship as the academy has been at recognizing on-line criticism as a legitimate mode of investigation. Canadian experimental feminist authors and artists, however, are proving more likely to embrace the philosophy, if not necessarily the medium, of electronic possibilities. The potential for cutting edge hypertext feminist scholarship is examined through an examination of Nicole Brossard's use of Virtual Reality as a feminist discourse in her novel Baroque at Dawn (Baroque d'aube) and Catherine Richards' body-based, real time art explorations in her Virtual Reality installation pieces entitled The Virtual Body and Curiosity Cabinet, at the End of the Millennium.